Studi Lesi Makroskopis dan Mikroskopis Embrio Ayam yang Diinfeksi Virus Newcastle Disease Isolat Lapang yang Virulen - Hamdu Hamjaya Putra; Haryadi Wibowo; Tri Untari; Kurniasih Kurniasih (Jurnal Sain Veteriner, 2012)
Newcastle disease (ND) is caused by Avian paramyxovirus, family Paramyxoviridae, one of the major diseases in chickens. This research was aimed to find lesions in chicken's embryo organs macroscopically andmicroscopically, infected by pathogenic ND virus. Embryonic chicken eggs (ECE) were inoculated by the ND Salatiga virus and ND La Sota virus as a control avirulent virus. Aquabidestilata used as a negative control. ECEwich showed the death of the embryos, stored in the refrigerator. The allantois fluid was collected, for further examination of viral growth. Chicken embryos that died then observed macroscopically. The organs of chicken embryos were made into histopathologic preparations stained with Hematoxylin and Eosin (H&E) for microscopic analysis. The identification of ND virus growth on isolates was done by haemagglutination andhaemagglutination inhibition test using an anti-ND serum. The chicken embryos that were infected by the ND Salatiga virus died approximately 26 hours post-inoculation. Macroscopic lesions were visible as haemorrhagein the skin. Microscopic lesions indicated the congestion and haemorrhage in lungs, inflammation and congestion in the skin, congestion in intestines, liver, kidneys and heart. There was also mild congestion on theskin in chicken embryos infected by ND La Sota virus. The microscopic lesions showed congestion in lungs, liver, kidneys and heart, also the inflammation and congestion on the skin. The macroscopic and microscopic lesions of chicken embryos infected by the ND Salatiga virus were more severe than lesions caused by ND La Sota virus.Key words: Newcastle disease, chicken embryos, macroscopic lesions, microscopic lesions, La Sota